BODY IMAGE ANAK USIA 5-6 TAHUN DALAM STIMULASI BONEKA MANUSIA - Bunga Putri Pratiwi (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2009)
The objective of this research is to describe about body image of 5-6 years old children in Human Doll Stimulation that include human doll stimulation process, doll choosen by children to be played with, wanted physical character when children grow up, child's opinion about self physical condition, inspiring figure for children about physical beauty (beautiful or handsome), how parents and teachers grow a positive body image to children. This research was held in Early Childhood Education (PAUD) Cikita, Bogor. This research was foccused on Matahari class (class of 4-6 years old chilren) and implemented qualitative method. Data collecting was done with triangulation, which consists of interview, observation, and documentation. Data analyzing was done by transcripting, data organizing, recognition, and coding. Result of this research found that: (1) human doll stimulation process started with children choose dolls they wanted, enrobe clothing and accessories, role play. (2) the selected dolls of children for a puppet play is a representation of the human adult than baby dolls. Physical doll that children preferred are well-lean and white doll, (3) the desired physical characteristics by female children when they grow-up are well-lean and white, the desired physical characteristics of male children when they grow-up are are well-lean / muscular and white, (4) children's opinion about their own physical and well-colored fat (5) figures that inspired children about physical beauty (beautiful / handsome) is a fictional character from television as Cinderella, Barbie, the army, siblings and a cousin that phisically attractive(6) how teachers and parents instill a positive body image in children's materials in the body, body functions, religious approach, masculinitiy learning. Implications of this research is the emergence of cooperation between parents, schools, teachers, directorates of the Early Childhood Education in implementing a positive body image in children, can also be used as a discourse for the readers, especially for next researchers.